(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out how to evaluate the Cash Social Assistance Policy for Community Welfare during the Covid-19 Pandemic in KalukuBodoa Village, Tallo District, Makassar City. The number of informants was 8 people. This study used qualitative with the type of descriptive research. Data collection techniques were observation, interviews, and documentation. Data analysis used data reduction, data presentation, and data levers. This study used William Dunn’s policy evaluation theory, with the results of the study showed that the BST program in KalukuBodoa Village had not been effective, implementation had achieved well. Adequacy: In overcoming the economy, the community could ease the burden during the COVID-19 pandemic, but it had not resolved their welfare problems. Equity: the costs and benefits of BST were distributed equally to the community. Responsiveness: The response from the community in KalukuBodoa Village were very good. Accuracy: The target of the BST program was not quite right, because there were still people who were more entitled to receive and there were people who got more than one assistance. But in terms of help it was right. Keywords : Evaluation, Social Assistance.